The effect of MgO and SiO2 codoping on the properties of Nd:YAG transparent ceramic - Yang, Hao (2013)
Nd:YAG transparent ceramics were fabricated by a reactive sintering method under vacuum using SiO2, MgO and compound additives (SiO2 and MgO) as sintering aids. The effects of SiO2 and MgO on the microstructure and sintering process of Nd:YAG ceramics were studied. High quality Nd:YAG ceramics with compound sintering aids obtained by vacuum sintering at 1780 °C are composed of grains of the size ∼10 μm, and their transmittance is 82% at 400 nm. It was found the absorption coefficient of 1.0 mol% Nd:YAG ceramic was 8.6 cm−1 at 808 nm and its absorption cross section was calculated to be 6.26 × 10^−20 cm2.